2008
DOI: 10.1002/jmv.21211
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of murine cytomegaloviruses with insertional and deletional mutations in the M34 open reading frame

Abstract: A viable virus could not be recovered from a mutant murine cytomegalovirus (MCMV) BAC in which the M34 ORF had been deleted (BACDeltaM34). In contrast, an M34 mutant virus (RcM34), in which the M34 ORF was interrupted by transposon insertion at nt 44,827 of the Smith MCMV BAC, was attenuated in replication both in tissue culture and in SCID mice. Similarly, mutant virus Rc3'DeltaM34, in which the 3'-end was deleted from nt 44,724 to nt 45,647, produced similar replication kinetics in tissue culture to RcM34 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Contrary to our expectations based upon previous reports (Baluchova et al, 2008), plaque formation was observed after transfection of the M34-MCMV BAC into CIM cells and a couple of 'blind passages' , in which no CPE or plaque formation was apparent. First plaques were observed after 17 days.…”
Section: Generation Of M34-mcmv By Bac Mutagenesiscontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our expectations based upon previous reports (Baluchova et al, 2008), plaque formation was observed after transfection of the M34-MCMV BAC into CIM cells and a couple of 'blind passages' , in which no CPE or plaque formation was apparent. First plaques were observed after 17 days.…”
Section: Generation Of M34-mcmv By Bac Mutagenesiscontrasting
confidence: 99%
“…Previous studies showed that a transposon insertion mutant of M34 (in which the transposon inserted at position 44,827 of the MCMV genome corresponding to codon 582 of M34) as well as a truncation mutant lacking the coding sequence corresponding to the C-terminal amino acids 548-854 of pM34 were replication competent, while "following transfection of NIH/3T3 cells with this BAC construct no virus was recovered, despite many repeated attempts the full M34 knock-out BAC could not be reconstituted" (Baluchova et al, 2008). Intriguingly, the authors stated that "although characteristic virus CPE was evident in mutant BACinfected cells BAC-containing virus of sufficient yield to titrate, grow stocks or passage was not achieved" (Baluchova et al, 2008), suggesting that residual virus replication may have occurred even at that time -a bit like a viable but nonculturable (VBNC) state well-known for certain bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations